PL.03 Self-Administration of Misoprostol to Prevent Bleeding After Homebirths in Uganda: A Pilot Placebo-Controlled, Randomised Trial. (26th April 2013) - Weeks, A; Ditai, J; Ononge, S; Durocher, J; Faragher, B; Byamugisha, J; Frye, L; Mirembe, F; Winikoff, B; Alfirevic, Z
Abstract : Objective: To pilot a study of self-administered misoprostol after home delivery for postpartum haemorrhage (PPH) prevention. Design: A pilot placebo-controlled, double-blind randomised trial Participants: Pregnant women at least 34 weeks of gestation living in Mbale district Uganda were recruited at four health facilities. High-risk women and women planning to deliver in facilities were included. Intervention: Pregnant women attending the clinics over a 2-month period were randomised to receive either misoprostol (600 µg) or identical placebo to be self-administered orally only if they did not reach a facility for delivery. Each woman was trained on medication use and the importance of PPH. After delivery, the women were visited at home and outcome and safety data collected. Results: 748 women were randomised to either 600 µg misoprostol (n = 374) or placebo (n = 374). 93% of women were followed up and 80% of drug packets (both used and unused) were retrieved. 56.7% of women took the study medication. Medication was taken before delivery in 2 women (both in the misoprostol group) and no harm was reported. The primary outcome (fall in Hb >20%) occurred in 7.3% of recruits. There were no significant differences between the groups in the rate of postnatal anaemia or self-reported blood loss. There was significantly more self-reported fever and shivering in the misoprostol group but acceptability of side effects was high. Conclusion: A randomised trial of self-administered misoprostol is feasible, and the pilot did not reveal major safety concerns with advanced distribution of misoprostol for self-administration.